Detection of SpaP and vicR genes in non-biofilm producing Streptococcus mutans isolated from dental caries and plaque - Aljubouri, Sahira A. (Tanjong Malim, 2024)
Detection of SpaP and vicR genes in non-biofilm producing Streptococcus mutans isolated from dental caries and plaque by Aljubouri, Sahira A.